Utilisasi Probiotik Cair Asal Fermentasi Black Soldier Fly Larvae (Hermetia illucens) terhadap Performa Ayam Broiler: Utilization of Liquid Probiotics from Black Soldier Fly Larvae (Hermetia illucens) Fermentation on Broiler Chickens Performance - Sukiman, Deva Latifa; Mutia, Rita; Martin, Rima Shidqiyya Hidayati; Nahrowi; Utari, Tazkiyah Annisa; Shofiah, Maya; Nugroho, J E (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to evaluate the utilization of liquid probiotics from black soldier fly larvae (BSFL) fermentation on broiler chickens' performance. A total of 250 male broilers strain Cobb CP 707 were given 5 treatments of probiotics in drinking water with 5 replications using a completely randomized design. The treatments in this study were P0=commercial broiler feed+drinking water without probiotics, P1=commercial broiler chicken feed+ drinking water with 1 mL L-1 commercial probiotic, P2=commercial broiler chicken feed+water with 1 mL L-1 probiotics from BSFL fermentation, P3=commercial boiler chicken feed+water with 3 mL L-1 probiotics from BSFL fermentation, and P4=commercial broiler chicken feed+water with 5 mL L-1 probiotics from BSFL fermentation. The results showed that BSFL fermentation probiotics were not significantly different on broiler chicken performance. Income over feed and chick cost (IOFCC) in addition to 5 mL L-1 in drinking water was more efficient in saving feed cost and the highest performance index during the broiler rearing. In conclusion, the utilization of BSFL fermentation probiotics in drinking water gave the same effect on broiler chicken performance as the other treatments yet the IOFCC and broiler chicken performance index were more advantageous. Key words: black soldier fly larvae, broiler, performance, probiotics